Bebida energizante a base de los extractos de la planta SUNFO (clinopodium nubigenum), flores de Ñachag (bidens andícola) y hojas de Guayusa (ilex Guayusa). - Naranjo Shunta, Cesar Esteban (2019)
The purpose of this research project is based on obtaining a natural energizing drink based on extracts of the sunfo plant, ñachag flowers and guayusa leaves, guayusa leaves were used to increase caffeine; previously in a chromatographic analysis, sunfo and ñachag did not contain caffeine, due to caffeine is the most important element to elaborate the energizing drink, which must contain at least a quantity of 33.94 mg /L compared with commercial energy drinks that fluctuates caffeine between 250 mg /L -350 mg /L according to NTE INEN 2411:2008 Energy drinks, an energizing drink was obtained in a low amount of sugar and calories so that sportmen can consume. To obtain the energizing drink, 8 treatments with two replicas were proposed. Proposing an arrangement of AxBxC factors under a DBCA in which factor A with two levels (concentration of raw materials),in factor B with two levels (type of sweetener) and in factor C with two levels (acidulant concentration), where a physicochemical analysis, proximal analysis and a chromatographic analysis were performed by means of these analyzes, the two replicas characteristics were evaluated such as pH, Brix degrees, acidity, nutritional parameters such as calories and carbohydrates, in the chromatographic analysis of the caffeine content to establish the best treatments those that were t8 (40% sunfo, 20% ñachag flowers and 40% guayusa leaves + hydrolyzed agave honey + citric acid 3 g), t6 (40% sunflower, 20% ñachag flowers and 40% leaves of guayusa + sucralose + citric acid 3g), t2 (35% of sunflower, 30% of flowers of ñachag and 35% of leaves of guayusa + Sucralose + Citric acid 3 g), considering a sensory analysis with 72 panelists from the UTC Club through an organoleptic evaluation of the energy drink determine the characteristics such as color, smell, taste, sweetness and acceptability to determine the best treatment which was t2 (35% sunfo, 30% ñachag flowers and 35% guayusa leaves + Sucralose + citric acid 3 g) taken to a process of reception of raw material, washing, sorting, disinfection, freezing, dehydration at 45° C for 4 hours, weighing dehydrated materials, grinding dehydrated raw materials, preparation of the concentration of samples where 2 g was made for 200ml of energizing drink influencing in the content of caffeine was also prepared in the two raw materials, infusion for 20 min at 65 ° C, mixed all the ingredients: sunfo extract, guayusa and ñachag, sweetener and acidulant, pasteurization at 75 ° C x 3 min, addition of cream of tartar as gasifier, packaging, sealing, labeling and storage. In addition, a physicochemical, nutritional, chromatographic and microbiological analysis of the energy drink was carried out in comparison with the NTE INEN 2411: 2008 of energy drinks, which through a report of results allows to deduce that it is within the range according to the NTE which guarantees the safety and food safety to the potential consumer of the Sunfpower energy drink.